Awareness × Opportunity: Testing Interactions Between Activity Nodes and Criminal Opportunity in Predicting Crime Location Choice. (5th October 2017) - Menting, Barbara
Abstract: According to crime pattern theory, offenders likely commit crimes in areas where their awareness space overlaps with criminal opportunity. If both are necessary conditions for crime to take place somewhere, their influence on crime location choice likely depends upon one another. Interactions between two activity nodes—residential area of (1) offenders, (2) offenders' family—and two criminal opportunity indicators—number of bars/restaurants/hotels, collective efficacy—were tested and found ( N = 13, 088 any-crime-type offences committed by 5377 offenders): both residential area types were more often targeted than areas where offenders/family did not live, with no/lesser difference between low versus high criminal opportunity. Areas where offenders/family did not live were statistically significantly least often targeted when criminal opportunity there was low.